Efeitos do contaminante emergente triclosan sobre a função cardiorespiratória do matrinxã, Brycon amazonicus, em normóxia e durante hipóxia gradual - Martins, Nícolas Fernandes (Universidade Federal de São Carlos, 2018)
Many organic compounds present in bodies of water, called emerging contaminants, are not yet contemplated in Brazilian environmental legislation. Such compounds need to be evaluated for their high toxicity to living organisms, causing serious problems for ecosystems, animal and human health. Among these compounds, widely used, is triclosan (TCS). The increasing use of TCS by the industry and a variety of common household products, including detergents, toothpastes, soaps, among others, results in the release of large and increasing amounts of this compound in water bodies, which can affect the health and survival of organisms aquatic Brazilian legislation has established a maximum TCS concentration of 0.3% for personal care products, cosmetics and perfumes, but there is no established limit for maximum permissible concentrations in the different water bodies. Despite the concern with such contaminant, few works are addressing its physiological effects on aquatic organisms, particularly fish. The present study evaluated the effect of TCS on cardiorespiratory function in vivo and on the expression of cardiac proteins involved in the management of cardiac calcium of Brycin amazonicus. Among the main findings, the present study showed that: a) in the presence of TCS the water does not reach 100% saturation with O2; b) TCS not only reduces the metabolic rate but also increases the critical O2 uptake, reducing the ability to keep O2 uptake constant and, consequently, reducing the chances of survival in hypoxic environments; c) the ventilatory requirement is significantly increased by the TCS, showing a significant decrease in the efficiency of the gills in the exchange of O2 besides increasing the energy expenditure for the gas exchange; d) TCS had a depressant effect on heart rate and increased expression of L-type calcium channels and Na + / Ca 2+ exchanger. Together, the results obtained in the present study show that the TCS, even in low concentrations and in short exposures (96h), decreases respiratory capacity of the species and interferes in the management of cardiac calcium. The depressant effect of cardio-respiratory function in vivo as well as changes in the expression of proteins involved in the cardiac excitation-contraction coupling of matrinxã reinforce the need not only for reassessment of the use of SCC in consumer products but also for the establishment of maximum limits waters for human consumption and conservation of aquatic life.
Effects of the emerging triclosan contaminant on the matrinxan cardiorespiratory function, Brycon amazonicus, in normoxy and during gradual hippoxia
Keywords: Triclosan; Matrinxã (Peixe); Respostas Cardiorespiratórias; Hipóxia; Cardiorespiratory responses; Hypoxia; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA